The role of literature and art in formation and humanization of a future doctor’s individual qualities - A. F. Sokol; R. V. Shurupova (Сеченовский вестник, 2022)
The article under review deals with the problem of studying literature and art in the medical high school; the author discusses the role of the Humanities in educational process of formation of physician’s professional competences.